How Changes in BenefitsEntitlement Affect Job-Finding : Lessons from the Slovenian "Experiment" - Milan Vodopivec; Jan C. van Ours (Institute for the Study of Labor (IZA), 2004)
In 1998 the Slovenian UI system was drastically reformed. The reform reduced the potential duration of unemployment benefits substantially and simultaneously improved employment services offered to, and monitoring of, the recipients. We find that the reduction in potential benefit duration had a positive effect on the exit rate out of unemployment – both to employment and to other destinations – at various durations of unemployment spells and for many categories of unemployed workers. We also identify a clear spike in the exit rate out of unemployment in the month unemployment benefits expire (and a smaller spike in the month thereafter), and for males an increase of job-finding rate in the third month of unemployment, a likely consequence of a reduction of the level of benefit that occurs at that point. Interestingly, post-unemployment wages of recipients were not affected after the change of the law, suggesting that higher job-finding rates following the reduction of benefits were not produced by reduced reservation wages (higher acceptance probability) but rather more effective job-search activity.
Keywords: H55; J64; J65; C41; 330; unemployment insurance; potential benefit duration; job finding rates; postunemployment wages; Arbeitslosenversicherung; Reform; Arbeitsangebot; Beschäftigungseffekt; Lohn; Wirtschaftspolitische Wirkungsanalyse; Slowenien